Current status and future perspectives of proton exchange membranes for hydrogen fuel cells - Jamil, A. (Elsevier Ltd, 2022)
The world is on the lookout for sustainable and environmentally benign energy generating systems. Fuel cells (FCs) are regarded as environmentally friendly technology since they address a variety of environmental issues, such as hazardous levels of local pollutants, while also delivering economic advantages owing to their high efficiency. A fuel cell is a device that changes chemical energy contained in fuels (such as hydrogen and methanol) into electrical energy. A wide variety of FCs are commercially available; however, proton exchange membranes for hydrogen fuel cells (PEMFCs) have received overwhelming attention owing to their potential to significantly reduce our energy consumption, pollution emissions, and reliance on fossil fuels. The proton exchange membrane (PEM) is a critical element; it is made of semipermeable polymer and serves as a barrier between the cathode and anode during fuel cell construction. Additionally, membranes function as an insulator between the cathode and anode, facilitating proton exchange and inhibiting electron exchange between the electrodes. Due to the excellent features such as durability and proton conductivity, Nafion membranes are commercially viable and have been in use for a long time. However, Nafion membranes are costly, and their proton exchange capacities degrade over time at higher temperatures and low relative humidity. Other types of membranes have been considered in addition to Nafion membranes. This article discusses the problems connected with several types of PEMs, as well as the strategies adopted to improve their characteristics and performance. Â© 2022 Elsevier Ltd